Penerapan Metode Shared Reading Untuk Meningkatkan Kemampuan Membaca Nyaring Siswa Di Kelas Tinggi - Prilly Yasinta Yasinta; Luthfi Hamdani Maula; Din Azwar Uswatun (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This study aims to describe the application method of Shared Reading  to improve the reading ability in high basic students. The research method used was Classroom Action Research with a research design using the Kemmis and Mc Taggart models which were carried out in two cycles. Each cycle consists of planning, implementing actions, observing, and reflecting. The subjects in this study were grade IV students of SDN 1 Cikembar with 39 students, consisting of 17 male students and 22 female students. Data collection techniques in this study used a test technique in the form of pretest and posttest. While the non-test technique is in the form of observation, field notes and documentation. The data analysis technique used is quantitative descriptive. The results of the pre-cycle study through the indicator test of the ability to read aloud, showed completeness of 26%. Then increasing in the first cycle reached completeness by 46%. Whereas in the second cycle, the results of the tests showed completeness reached 79%. This Classroom Action Research concludes that students ability to read aloud increases through Shared Reading methods in high school students in the elementary school year 2019.